PROFIL PENDERITA ULKUS DEKUBITUS YANG MENJALANI TIRAH BARING DI RUANG RAWAT INAP RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2011-DESEMBER 2013 - Levina Mutia; Kuswan Ambar Pamungkas; Dewi Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTPressure ulcer is one of complication that might happen in Integumen System. It is formed because of the inability to mobilize in patient during bed rest. In addition, the incidence of pressure ulcer is one of indicator to evaluate hospital’s service quality. The incidence of pressure ulcer is associated with the service control and quality for patients. This research was aimed to know the profile of patient with pressure ulcer that experience bed rest at inpatient room of Riau Province General Hospital during January 2011-December 2013. It comprises of the patient’s distribution based on age, sex, diagnose that caused bed rest, the first day of ulcer appeared, ulcer stage and the therapy. The research was an observational study using descriptive retrospective design. This study used total sampling method. Samples of this study were all data of pressure ulcer patient that fulfilled inclusion criteria. The total samples were 54 cases. This study shows that the age group of 46-65 years old (51.9%) and female (64.8%) in sex group were the most commonly patient with pressure ulcer. Stroke was the top of diagnose that caused pressure ulcer with 53.7% in percentage. Pressure ulcer stage 1 and 4 with 33.3% in percentage each were the most commonly stage that has been found. Pressure ulcer was appeared on day 9 in the average and mostly appeared on day 7. Non-operative therapy (87%) is often used for treating patient with pressure ulcer.Keywords: Pressure Ulcer, Bed Rest